Chronic copper toxicosis in a crossbred heifer calf. (May 2020) - Wong, Agnes; Wilson-Frank, Christina R.; Hooser, Stephen B.; Burcham, Grant N.
An 8-mo-old, crossbred, heifer calf was presented to the Heeke Animal Disease Diagnostic Laboratory with a history of ataxia and altered mentation. Grossly, the liver was diffusely yellow-orange, turgid, and exuded watery, thin blood on cut section. The cortex and medulla in both kidneys were diffusely and markedly dark brown to black. The urinary bladder was filled with dark red urine. Histologically, centrilobular hepatocellular degeneration was observed, but these sections lacked necrosis. In the kidney, numerous cortical tubules contained intraluminal bright eosinophilic fluid and red-orange granular casts that stained positive for hemoglobin with the Dunn–Thompson method. The gross and histologic lesions supported a high level of suspicion for copper toxicosis. Feed and water samples from the farm were submitted for mineral analysis. The copper concentration in the feed was 118 mg/kg, and the molybdenum concentration was 0.9 mg/kg. Chronic copper toxicosis is rarely reported in cattle. The gross lesions in our case are a departure from, although similar to, previously reported cases, including lack of histologic hepatocellular necrosis. Collectively, gross and histologic lesions were compatible with copper toxicosis in this calf, and copper concentrations in the feed samples suggest a feed-mixing error.